Preparation and application of lightweight blocky Ru / ZIF-67 / PMF composite material

By growing ZIF-67 on the MF surface of melamine foam and modifying PVA, lightweight block Ru/ZIF-67/PMF composites were prepared, which solved the problem of structural damage during the catalyst easy agglomeration and recovery process, and achieved efficient catalysis and stability improvement.

CN119500274APending Publication Date: 2025-02-25GUILIN UNIV OF ELECTRONIC TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411661181.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing catalysts have problems such as complex devices, easy catalyst agglomeration, and damage to the microstructure of the material during recycling. The large density of the bulk carrier material leads to low catalytic efficiency and low binding strength between the support and metal clusters.

Method used

Using melamine foam MF as a carrier, a 3D porous structure was formed by growing ZIF-67 on its surface, and the binding strength between the carrier and nanoparticles was improved through PVA modification, and a lightweight block Ru/ZIF-67/PMF composite material was prepared.

Benefits of technology

The specific surface area and active sites of the catalyst are improved, the catalytic efficiency is enhanced, the process difficulty of the recovery process and the damage to the micromorphology of the material are reduced, and the stability and circulation performance of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500274A_ABST
    Figure CN119500274A_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight blocky Ru / ZIF-67 / PMF composite material, which is characterized in that melamine foam PMF treated by polyvinyl alcohol PVA is used as a carrier, ZIF-67 is grown on the surface of PMF to prepare ZIF-67 / PMF, Ru nanoparticles are loaded by a chemical reduction method to obtain the Ru / ZIF-67 / PMF lightweight blocky composite material with a macroscopic blocky structure, and controllable on-demand hydrogen desorption can be realized by controlling the height of the block. The preparation method comprises the following steps: 1, preparing PMF; (2) preparation of ZIF-67 / PMF (Zinc Ionic Factor); and 3, preparation of the Ru / ZIF-67 / PMF. When the catalyst is used as a sodium borohydride hydrolysis hydrogen production catalyst, under the condition of 303K, the maximum hydrogen production rate is 6000-7000 mL * min <-1 > * g <-1 >, and the hydrogen desorption amount is 100% of a theoretical value; after circulation is carried out for 5 times, 80.7-91.5% of the initial maximum hydrogen production rate is still kept; the apparent activation energy Ea of the reaction is 20.9 to 25.3 kJ.mol <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyzing the hydrolysis of sodium borohydride to produce hydrogen, and in particular to the preparation and application of a light block Ru / ZIF-67 / PMF composite material. Background Art

[0002] Among the numerous hydrogen energy materials, sodium borohydride NaBH4 is widely considered to be the best choice for green hydrogen production due to its high hydrogen storage capacity of 10.8wt%, as well as its renewability, environmental friendliness and low raw material cost. However, the technical problem of NaBH4 is that its slow reaction kinetics of self-hydrolysis limits its practical application. In order to solve the problem of slow hydrolysis reaction kinetics, the reaction rate can be increased by adding a catalyst to achieve rapid hydrogen precipitation.

[0003] At present, the catalysts with the best catalytic performance for the NaBH4 hydrolysis reaction are mainly precious metal catalysts - precious metals Pt, Pd, Ru and Rh can significantly improve the maximum hydrogen production rate HGR of NaBH4 hydrolysis. For example, the existing literature 1 (Tuan DD, Lin KY A. Ruthenium supported on ZIF-67 as an enhanced catalyst for hydrogen generation from hydrolysis of sodium borohydride [J]. Chemical Engineering Journal, 2018, 351: 48-55.) synthesized Ru / ZIF-67 nanopowder catalyst by chemical reduction method, which can reach 5520mL·min at 30°C. -1 ·g -1 and 22,400 mL·min at 60°C -1 ·g -1 This technical solution has achieved good performance in catalyzing the hydrolysis of borohydride. However, powdered catalysts represented by this technical solution all have problems of complex equipment, catalyst agglomeration during use, and destruction of the microstructure of the material during the recovery of the catalyst after use.

[0004] Compared with the above-mentioned powdered catalysts, block catalysts can effectively solve the above-mentioned agglomeration and recycling problems, and also have the characteristics of controllable hydrogen production. Therefore, the current solution is to introduce blocky carrier materials to load nanocatalysts. For example, existing literature 2 (Guo J, Wu C, Zhang J, et al. Hierarchically structured rugae-like RuP3-CoP arrays as robust catalysts synergistically promoting hydrogen generation [J]. Journal of Materials Chemistry A, 2019, 7 (15): 8865-8872.) assembled an array of Co-Ru-P catalysts as borohydride hydrolysis catalysts on the skeleton surface of nickel foam by electrodeposition and phosphating. The maximum hydrogen production rate of the macroscopic block catalyst obtained by this technical solution at 25°C is 4839.8 mL min -1 g -1 , and through simple immersion recovery, the cycle retention rate was 92% when the number of cycles was 5. This technical solution can increase the specific surface area and porosity due to the 3D porous skeleton structure of nickel foam, thereby solving the agglomeration problem of powdered micro-nano catalysts and enhancing solute transport and gas diffusion. However, this type of technical solution based on nickel foam as a carrier material has a new technical problem - the density of nickel foam is 0.5-2g / cm 3 Due to the high density of nickel foam itself, it directly leads to the technical problem of low catalytic efficiency per unit mass after loading the catalytic active material.

[0005] The above-mentioned problem of unit mass catalytic efficiency can be solved by using low-density materials as carriers. Among them, melamine sponge MF has the same advantages as foamed nickel in terms of high porosity and diverse structures, and its density is only 0.004-0.012g / cm 3, that is, it has the characteristics of low density. However, when MF is used as a carrier material, there is a problem of low binding strength with metal clusters and nanoparticles. This problem directly leads to a low loading amount of metal catalysts on MF, and there are problems of shedding and agglomeration. Therefore, when MF is used as a carrier, surface modification and functionalization are required. For example, existing document 2 (Feng Y, Wang Y, Wang Y, et al. In-situ gelation of sodium alginate supported on melamine sponge for efficient removal of copper ions [J]. Journal of colloid and interface science, 2018, 512: 7-13.) achieves the capture of Cu in wastewater by in-situ gelation of sodium alginate and MF sponge. 2+ The technical effect is to significantly increase the force of MF on metal particles. However, the gelation technology used in this technical solution directly leads to a significant increase in the density of the carrier MF, that is, the basic characteristics of a lightweight material are lost.

[0006] Therefore, the existing technology currently has the following technical problems:

[0007] 1. Conventional powder catalysts have the problems of complicated use equipment, easy agglomeration of catalysts during use, and destruction of the microstructure of the material during the recovery of the catalyst after use;

[0008] 2. The density of the commonly used block carrier material is high, which directly leads to the problem of low catalytic efficiency per unit mass after the catalytic active substance is loaded;

[0009] 3. While keeping the low-density block carrier lightweight, increase its loading capacity with metal clusters and nanoparticles and improve the bonding strength. Summary of the invention

[0010] The purpose of the present invention is to provide a preparation and application of a lightweight blocky Ru / ZIF-67 / PMF composite material. In view of the technical problems existing in the current technology, the following principles and methods are used to solve the above problems:

[0011] 1. The present invention uses MF as a carrier to load ZIF-67 to form a 3D porous structure, thereby improving the problem of easy accumulation of metal organic framework materials, increasing the specific surface area of ​​the composite material, increasing the active sites, and obtaining the technical effect of increasing HGR;

[0012] 2. The present invention uses MF as a carrier to increase the proportion of catalytically active substances, that is, to obtain a light catalyst;

[0013] 3. The present invention uses PVA to modify MF as a carrier, and introduces functional groups on the surface of MF to improve the interaction between MF and nanoparticles, providing in-situ growth sites and anchoring effects;

[0014] 4. The present invention uses MF as a carrier to achieve a block structure of the composite material. By replacing the traditional suction filtration recovery method with immersion recovery, it can effectively improve the problems of oxidation and shedding during its use, greatly reduce the process difficulty of the recovery process and the damage to the microscopic morphology of the material, and improve the stability of the catalyst.

[0015] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0016] A lightweight block Ru / ZIF-67 / PMF composite material, using melamine foam PMF treated with polyvinyl alcohol (PVA) as a carrier, first growing ZIF-67 on the surface of PMF to obtain ZIF-67 / PMF, and then loading Ru nanoparticles through a chemical reduction method to obtain a Ru / ZIF-67 / PMF lightweight block composite material;

[0017] The raw materials of the PMF are melamine foam, polyvinyl alcohol, formaldehyde and sulfuric acid;

[0018] The raw materials of ZIF-67 are cobalt nitrate hexahydrate and 2-methylimidazole;

[0019] The raw materials of Ru are ruthenium trichloride hydrate and sodium borohydride;

[0020] The microstructure of the Ru / ZIF-67 / PMF is a 3D porous structure, and a rhombic dodecahedron structure with a size of 500-800 nm is grown and coated on the surface of PMF. The component of the rhombic dodecahedron structure is ZIF-67. Ru nanoparticles are used as active materials and are loaded on the surface of ZIF-67 by in-situ reduction of sodium borohydride.

[0021] The obtained Ru / ZIF-67 / PMF is a macroscopic block structure, and controllable on-demand hydrogen release can be achieved by controlling the height.

[0022] A method for preparing a lightweight bulk Ru / ZIF-67 / PMF composite material comprises the following steps:

[0023] Step 1, preparation of PMF, first, polyvinyl alcohol PVA and deionized water are mixed, and mixed and stirred under certain conditions to obtain solution A; then, formaldehyde, sulfuric acid and solution A are mixed to obtain solution B; thereafter, melamine foam MF is placed in solution B, and allowed to stand under certain conditions so that MF absorbs solution B to obtain polyvinyl alcohol melamine foam PVA-MF; finally, under certain conditions, PVA-MF is subjected to co-acetalization cross-linking reaction, and after the reaction is completed, the reaction product is washed with water and ethanol, and then vacuum dried under certain conditions to obtain PMF;

[0024] In the step 1, the mass ratio of PVA, formaldehyde, sulfuric acid and MF is 1:2:1:(5-10);

[0025] In step 1, the conditions for preparing solution A are: mixing temperature is 80-100° C., and mixing time is 3-6 h;

[0026] In the step 1, the strips of solution B are allowed to stand for a period of 0.5-1 h;

[0027] In step 1, the conditions for the co-acetalization cross-linking reaction are: a heating temperature of 80-100° C. and a heating time of 3-6 h;

[0028] In step 1, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-12 h;

[0029] Step 2, preparation of ZIF-67 / PMF, PMF obtained in step 1 and cobalt nitrate hexahydrate are placed in methanol, and an operation of first ultrasonication and then standing is performed under certain conditions to obtain solution C; in addition, 2-methylimidazole is placed in methanol to obtain solution D; then, solution D is quickly added to solution C, and an operation of first stirring and then standing is performed under certain conditions to obtain product E; finally, product E is washed with water and ethanol, and then vacuum dried under certain conditions to obtain ZIF-67 / PMF;

[0030] In the step 2, the mass ratio of PMF, cobalt nitrate hexahydrate and 2-methylimidazole is (1-4):60:(20-40);

[0031] In step 2, the conditions for preparing solution C by ultrasonication and then standing are as follows: the ultrasonication time is 30-60 min and the standing time is 12-24 h;

[0032] In step 2, the conditions for preparing solution C by stirring first and then standing are: the stirring time is 2-3 hours and the standing time is 12-24 hours;

[0033] In step 2, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 12-24 hours;

[0034] Step 3, preparation of Ru / ZIF-67 / PMF, dispersing the ZIF-67 / PMF obtained in step 2 in deionized water, adding ruthenium trichloride hydrate, performing an operation of ultrasonicating and then standing under certain conditions to obtain solution F, then, under certain conditions, dropping a sodium borohydride solution into solution F, after the dropping is completed, standing under certain conditions again, after the standing is completed, washing the obtained product with ethanol, and vacuum drying under certain conditions to obtain a lightweight block Ru / ZIF-67 / PMF composite material;

[0035] In step 3, the mass ratio of ZIF-67 / PMF, ruthenium trichloride hydrate and sodium borohydride solution is 10:(1-2):(5-10);

[0036] In step 3, the conditions for preparing solution F by first ultrasonicating and then standing are as follows: the ultrasonication time is 30-60 min and the standing time is 12-24 h;

[0037] In step 3, the conditions for adding sodium borohydride dropwise are: the ice bath temperature is 2-6° C., the drop rate is 3-5 drops / s, and the concentration of sodium borohydride is 0.5-1 M;

[0038] In step 3, the standing condition is that the standing time is 12-24 hours;

[0039] In step 3, the vacuum drying conditions are as follows: the drying temperature is 80-100° C. and the drying time is 12-24 hours.

[0040] A lightweight bulk Ru / ZIF-67 / PMF composite material, when used as a catalyst for hydrogen production from sodium borohydride hydrolysis, has a maximum hydrogen production rate of 6000-7000 mL·min at 303K -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value; the apparent activation energy of the reaction is E a =20.9-25.3 kJ·mol -1 ; After five cycles at 303K, 80.7-91.5% of the initial maximum hydrogen production rate was still retained.

[0041] The technical effect of the present invention can be known by the following tests:

[0042] The density of Ru / ZIF-67 / PMF is 0.136 g / cm 3 , that is, lightweight material;

[0043] The present invention has successfully synthesized Ru / ZIF-67 / PMF material through XRD detection;

[0044] The EDS test of the present invention shows that the Ru, Co, C, N and O elements are evenly distributed in the Ru / ZIF-67 / PMF material;

[0045] According to the SEM test, the microstructure of the Ru / ZIF-67 / PMF material is a 3D porous structure, and a rhombic dodecahedron structure with a size of 500-800 nm is grown and coated on the surface of PMF, and the rhombic dodecahedron structure is ZIF-67; Ru nanoparticles are loaded on the surface of ZIF-67 by in-situ reduction of sodium borohydride, showing a uniform morphology of small grains;

[0046] The present invention has been tested for hydrogen production by hydrolysis and found that at 303K, the maximum hydrogen production rate is 6000-7000mL·min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value;

[0047] The present invention has been tested for reaction kinetics and found that the apparent activation energy E of the reaction is a =20.9-25.3 kJ·mol -1 ;

[0048] The present invention has been tested for hydrogen production by hydrolysis and found that: Ru / ZIF-67 / PMF is a macroscopic block structure, and controllable on-demand hydrogen release can be achieved by controlling the height;

[0049] The cycle performance test of the present invention shows that after 5 cycles at 303K, 80.7-91.5% of the initial maximum hydrogen production rate is still retained.

[0050] Therefore, the present invention has the following advantages:

[0051] 1. The present invention uses melamine foam MF as a carrier to ensure the lightness of the composite material, thereby increasing the proportion of catalytically active substances with catalytic effects and improving HGR;

[0052] 2. The present invention uses PVA-modified MF as a carrier, and the rich functional groups on its surface can attract and control the nanoparticles to bind to it, provide in-situ growth sites, and play an anchoring role at the same time;

[0053] 3. The present invention introduces ZIF-67, which improves the uniformity of the material while also inhibiting the agglomeration of the material, effectively increasing the contact area between Ru nanoparticles and NaBH4, thereby increasing the maximum hydrogen production rate of the catalyst;

[0054] 4. The present invention adopts melamine foam MF as a carrier to realize the block structure of the composite material. The immersion recovery replaces the traditional suction filtration recovery method, which can effectively improve the problems of oxidation and shedding during its use, greatly reduce the process difficulty of the recovery process and the damage to the microscopic morphology of the material, and improve the stability of the catalyst.

[0055] 5. The raw materials used in the present invention are all industrially produced chemical raw materials, which are available in the market and easy to obtain. The process for synthesis is simple, the reaction cycle is short, the reaction process has low energy consumption and low pollution.

[0056] Therefore, compared with the prior art, the present invention has better catalytic performance for producing hydrogen by hydrolysis of sodium borohydride, improves the stability of the catalyst, and has broad application prospects in the fields of hydrogen production materials, fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 Density comparison diagram of MF, PMF, ZIF-67 / PMF and Ru / ZIF-67 / PMF in Example 1;

[0058] Figure 2 FT-IR images of MF, PMF, ZIF-67 / PMF and Ru / ZIF-67 / PMF in Example 1;

[0059] Figure 3 is the SEM image of PMF in Example 1;

[0060] Figure 4 XRD patterns of ZIF-67 / PMF and Ru / ZIF-67 / PMF in Example 1;

[0061] Figure 5 It is the SEM image of ZIF-67 / PMF in Example 1;

[0062] Figure 6 is the EDS image of Ru / ZIF-67 / PMF in Example 1;

[0063] Figure 7 It is the SEM image of Ru / ZIF-67 / PMF in Comparative Example 1;

[0064] Figure 8 The Ru / ZIF-67 / PMF in Example 1 catalyzes sodium borohydride hydrolysis at different temperatures;

[0065] Fig. 9 is the activation energy diagram of Ru / ZIF-67 / PMF in Example 1;

[0066] Fig.10 This is a diagram of the controllable on-demand hydrogen release of Ru / ZIF-67 / PMF in the cycle test of Example 1;

[0067] Fig.11 The cycle performance diagram of Ru / ZIF-67 / PMF in Example 1 catalyzing sodium borohydride hydrolysis and hydrogenation for 5 cycles at 303K;

[0068] Fig.12 It is a comparison chart of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, and Comparative Example 5 catalyzing the hydrolysis and hydrogenation of sodium borohydride at a temperature of 303K;

[0069] Fig.13 This is the SEM image of Ru / PMF in Comparative Example 2. DETAILED DESCRIPTION

[0070] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0071] Example 1

[0072] A method for preparing a lightweight blocky Ru / ZIF-67 / PMF composite material, the specific steps are as follows:

[0073] Step 1, preparation of PMF, first, 0.2g polyvinyl alcohol PVA and 10mL deionized water are mixed, and the mixture is stirred at a mixing temperature of 95°C and a mixing time of 6h to obtain solution A; then, 0.2mL formaldehyde, 0.1mL sulfuric acid and solution A are mixed to obtain solution B; thereafter, 0.01g melamine foam MF is placed in solution B, and the mixture is allowed to stand for 0.5h to allow MF to absorb solution B, thereby obtaining polyvinyl alcohol melamine foam PVA-MF; finally, PVA-MF is subjected to a co-acetalization cross-linking reaction at a heating temperature of 85°C and a heating time of 3h. After the reaction is completed, the reaction product is washed with water and ethanol, and then vacuum dried at a drying temperature of 80°C and a drying time of 12h to obtain PMF;

[0074] In order to prove that the PMF material obtained in step 1 is lightweight, a density test is performed. The test results are as follows: Figure 1 As shown in Table 1, the density of PMF is 0.08 g / cm 3 .

[0075] Table 1 Summary of density of different materials

[0076] catalyst <![CDATA[Density g / cm 3 > MF 0.001 PMF 0.080 ZIF-67 / PMF 0.120 Ru / ZIF-67 / PMF 0.136

[0077] In order to prove the structure of PMF obtained in step 1, i.e., successful cross-linking, FT-IR test was performed; at the same time, MF was measured by FT-IR as a reference. The test results are shown in Figure 2 As shown,

[0078] The test results of MF are as follows Figure 1 As shown, MF is at 1012cm -1 , and 2850-2950cm -1There is no characteristic peak caused by the stretching of the COC bond of the acetal group and the CH bond of the alkyl chain;

[0079] The test results of PMF are as follows: Figure 1 As shown, PMF is at 1012cm -1 , and 2850-2950cm -1 There are characteristic peaks caused by the stretching of the COC bond of the acetal group and the CH bond of the alkyl chain;

[0080] The test results show that PMF has CH and COC bonds compared with MF, which proves that co-acetalization reaction has occurred and cross-linking between PVA and MF has been achieved.

[0081] In order to verify the microstructure of the PMF material obtained in step 1, SEM test was performed. The test results are shown in Figure 3 As shown, the microstructure of PMF is a 3D porous structure.

[0082] Step 2, preparation of ZIF-67 / PMF, 0.08g of PMF obtained in step 1 and 1.0275g of cobalt nitrate hexahydrate are placed in 80mL of methanol, and an operation of ultrasonication is performed for 30min and a standing time is performed for 24h to obtain solution C; in addition, 2.32g of 2-methylimidazole is placed in 80mL of methanol to obtain solution D; then, solution D is quickly added to solution C, and an operation of stirring for 3h and a standing time is performed for 24h to obtain product E; finally, product E is washed with water and ethanol for 3 times, and then vacuum dried at a drying temperature of 60°C and a drying time of 12h to obtain ZIF-67 / PMF;

[0083] In order to prove that the material ZIF-67 / PMF obtained in step 2 is lightweight, a density test was performed. The test results are as follows Figure 1 As shown in Table 1, the density of ZIF-67 / PMF is 0.12 g / cm 3 .

[0084] In order to prove the composition of ZIF-67 / PMF obtained in step 2, XRD test was performed; at the same time, XRD test of ZIF-67 was performed as a reference. Figure 4 As shown, ZIF-67 / PMF has the same characteristic peaks as ZIF-67. The test results show that step 2 successfully prepared ZIF-67 on PMF.

[0085] In order to verify the microstructure of ZIF-67 / PMF obtained in step 2, SEM test was performed. The test results are shown in Figure 5As shown, the microstructure of PMF still maintains a 3D porous structure, and a rhombic dodecahedron structure with a size of 500-800nm ​​grows and covers the surface of PMF. Combined with the XRD test results, it can be seen that the rhombic dodecahedron structure is ZIF-67.

[0086] Step 3, preparation of Ru / ZIF-67 / PMF, disperse 0.1 g of ZIF-67 / PMF obtained in step 2 in deionized water, add 12 mg of ruthenium trichloride hydrate, perform ultrasonication first and then standing for 30 min and 24 h to obtain solution F, then, add 10 mL of 0.5 M sodium borohydride solution to solution F at an ice bath temperature of 2 ° C and a drop rate of 3 drops / s, after the addition is completed, stand for 12 h, after standing, wash the obtained product with ethanol, and vacuum dry at a drying temperature of 80 ° C and a drying time of 12 h to obtain a lightweight block Ru / ZIF-67 / PMF composite material, referred to as Ru / ZIF-67 / PMF.

[0087] In order to prove that the Ru / ZIF-67 / PMF material obtained in step 3 is lightweight, a density test was performed. The test results are as follows: Figure 1 As shown in Table 1, the density of Ru / ZIF-67 / PMF is 0.136 g / cm 3 .

[0088] In order to verify the composition of Ru / ZIF-67 / PMF obtained in step 3, XRD test was performed. The test results are shown in Figure 4 As shown in the figure, Ru / ZIF-67 / PMF and ZIF-67 / PMF have the same characteristic peaks. The test results show that the crystal structure is not affected by the reaction in step 3, but the characteristic peak of Ru element is not detected. The reason is that the content of Ru element is below the detection limit. Therefore, EDS test is carried out to verify the Ru element.

[0089] The EDS test results of Ru / ZIF-67 / PMF are as follows Figure 6 As shown in Figure 2, in addition to the C, O, N, and Co elements provided by ZIF-67 / PMF, Ru / ZIF-67 / PMF also contains Ru. The test results show that step 3 successfully loaded the responsible Ru element.

[0090] In order to verify the microstructure of Ru / ZIF-67 / PMF obtained in step 3, SEM test was performed. The test results are shown in Figure 7 As shown in the figure, the microstructure of Ru / ZIF-67 / PMF has no obvious change compared with ZIF-67 / PMF. The test results show that loading Ru element in step 3 has no substantial effect on the microstructure of ZIF-67 / PMF.

[0091] In order to prove the hydrogen production performance of Ru / ZIF-67 / PMF obtained in step 3 as a catalyst for hydrogen production by hydrolysis of sodium borohydride, a hydrogen production test by hydrolysis was carried out. The specific method of the hydrogen production test by hydrolysis is as follows: the hydrogen production test is carried out under the temperature conditions set in the experiment, a solution containing 1.5wt.% NaBH4 and 5wt.% NaOH is placed in a constant temperature water bath, and after reaching equilibrium at the aforementioned set temperature; 10mL is taken out and added to a wide-mouth bottle containing the catalyst, and the volume of hydrogen produced per unit time is collected and recorded by the drainage method, and the hydrogen release rate can be obtained, wherein the test temperature condition is 303K when not specifically stated.

[0092] The test results of hydrogen production by hydrolysis of Ru / ZIF-67 / PMF are shown in Table 1 and Figure 8 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 6292.52 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value.

[0093] Furthermore, in order to prove the reaction kinetics of Ru / ZIF-67 / PMF, hydrolysis hydrogen production tests were carried out at 298K, 308K, and 313K. The test results were fitted by the Arrhenius equation as shown in Table 1 and Fig. 9 As shown, the apparent activation energy of the reaction E a =22.91 kJ·mol -1 At the same time, in order to compare with the prior art, the data of the references are summarized in Table 1.

[0094] Table 2 Hydrogen production rate and activation energy of NaBH4 hydrolysis catalyzed by different catalysts

[0095]

[0096] Note: The reference numbers in Table 2 correspond to the following documents:

[0097] [1]Liu CH, Chen BH, Hsueh CL, et al. Hydrogen generation from hydrolysis of sodium borohydride using Ni-Ru nanocomposite as catalysts[J]. International journal of hydrogen energy, 2009, 34(5): 2153-2163.

[0098] [2]Avci Hansu T,Sahin O, A,et al.Untangling the cobalt promotionrole for ruthenium in sodium borohydride dehydrogenation with multiwalledcarbon nanotube-supported binary ruthenium cobalt catalyst[J].InternationalJournal of Energy Research,2021,45(4):6054-6066.

[0099] [3]Salih Keskin M, Horoz S.Efficiency of TiO2-supported Ni-Mo-Ru-B catalyst for hydrogen production from potassium borohydride hydrolysis[J].Journal of the Australian Ceramic Society,2022,58(3):973-979.

[0100] [4]Dinh TD,Andrew K Y.Ruthenium supported on ZIF-67as an EnhancedCatalyst for Hydrogen Generation from Hydrolysis of Sodium Borohydride[J].Chemical Engineering Journal, 2018,351:48-55.

[0101] The following conclusions can be drawn from the above test results and comparative analysis with existing references:

[0102] 1.1. Reference [1] is Ni-Ru metal nanoparticles, that is, the obtained material does not introduce a carrier, while reference [2] uses MWCNT as a carrier to load RuCo nanoparticles. By comparing reference [2] with reference [1], it can be seen that although reference [2] can reduce the activation energy Ea by introducing MWCNT as a carrier, it also greatly reduces the maximum hydrogen production rate;

[0103] 1.2. At the same time, by comparing reference [3] with reference [1], it can be seen that reference [3] introduces TiO2 as a carrier, which is contrary to reference [2]. Although it can effectively increase the maximum hydrogen production rate, the effect on the activation energy Ea is negligible;

[0104] Therefore, according to conclusions 1.1 and 1.2, different carriers may have different roles in composite materials, that is, there are substantial differences.

[0105] 2. According to reference [3], when ZIF-67 is used as a carrier, HGR can be increased and Ea can be reduced at the same time. The reason is that ZIF-67 is a metal-organic framework complex with the characteristics of high specific surface area and specific microstructure.

[0106] 3. Furthermore, by comparing the present invention with reference [3], it can be seen that the present invention introduces PMF as a carrier, which also has the technical effect of simultaneously increasing HGR and reducing Ea. However, compared with reference [3], it can be seen that PMF as a carrier has a negligible effect on the maximum hydrogen production rate, but can effectively reduce the activation energy Ea, which proves that the role of PMF in the technical solution is reflected in significantly reducing the activation energy Ea.

[0107] Based on the above analysis, the catalytic performance of the present invention is significantly improved compared with the prior art. The reasons are as follows:

[0108] 1. The present invention introduces MF as a carrier to provide support for ZIF-67 to form a 3D porous structure, which improves the disadvantage of easy accumulation of metal organic framework materials, ensures that the composite material has a large surface area and the active sites are clearly exposed; and enables the catalyst to have the technical effect of simultaneously increasing HGR and reducing Ea;

[0109] 2. The present invention uses PVA-modified MF as a carrier, and the rich functional groups on its surface can attract and control the nanoparticles to bind to it, provide in-situ growth sites, and play an anchoring role at the same time;

[0110] 3. The present invention introduces ZIF-67, which improves the uniformity of the material while also inhibiting the agglomeration of the material, effectively increasing the contact area between Ru nanoparticles and NaBH4, thereby increasing the maximum hydrogen production rate of the catalyst.

[0111] Since Ru / ZIF-67 / PMF is a macroscopic block structure, it can realize controllable on-demand hydrogen release by controlling the height. Therefore, in order to prove that Ru / ZIF-67 / PMF has the characteristics of controllable on-demand hydrogen release, a controllable on-demand hydrogen release hydrolysis test was carried out. The test results are as follows Fig.10As shown in the figure, when the block Ru / ZIF-67 / PMF is immersed in NaBH4 solution, the LED light is on, which means that stable H2 production is achieved; when Ru / ZIF-67 / PMF is separated from the NaBH4 solution, the LED light is off, which means that hydrogen release stops. The test results show that Ru / ZIF-67 / PMF has the characteristics of controllable on-demand hydrogen release.

[0112] According to the inventors' research, catalysts with macroscopic block structures can effectively improve cycle performance because they can be directly recovered, that is, without the need for conventional catalyst filtration or centrifugal recovery methods. Therefore, in order to prove the cycle performance of Ru / ZIF-67 / PMF, a cycle performance test was conducted. The specific method of the cycle performance test is as follows: First, the Ru / ZIF-67 / PMF that has been subjected to the hydrogen release test is recovered by simple immersion and rinsing treatment, and then the recovered Ru / ZIF-67 / PMF is subjected to the aforementioned hydrolysis hydrogen production test again to obtain the hydrogen release rate after the cycle, and finally, the cycle retention rate of Ru / ZIF-67 / PMF can be obtained by simple calculation. The test results are shown in Tables 2 and Fig.11 As shown in Figure 2, after five cycles at 303 K, the maximum hydrogen production rate was 5701.0 mL min -1 g -1 , the circulation retention rate is 90.6%. Compared with the conventional powder catalyst recovery by centrifugal filtration, the recovery method of the present invention can reduce the loss of catalyst and the damage to the microscopic morphology of the catalyst during the recovery process, thus improving the circulation retention rate.

[0113] In order to further demonstrate the cycle performance of the present invention, the data of the references are summarized in Table 3 by comparison with the prior art.

[0114] Table 3 Cycle number and cycle performance of NaBH4 hydrolysis catalyzed by different catalysts

[0115]

[0116] Note: The reference numbers in Table 3 correspond to the following documents:

[0117] [5]Li T, Xiang C, Chu H, et al. Catalytic effect of highly dispersedultrafine Ru nanoparticles on a TiO2-Ti3C2 support: Hydrolysis of sodiumborohydride for H2 generation. Journal of Alloys and Compounds, 2022,906:164380.

[0118] [6] Zhou S, Yang Y, Zhang W, et al. Structure-regulated Ru particles decorated P-vacancy-rich CoP as a highly active and durable catalyst for NaBH4 hydrolysis. Journal of Colloid and Interface Science, 2021, 591: 221-228.

[0119] [7]Guo J, Wu C, Zhang J, et al. Hierarchically structured rugae-likeRuP3-CoP arrays as robust catalysts synergistically promoting hydrogen generation[J]. Journal of Materials Chemistry A, 2019, 7(15):8865-8872.

[0120] The following conclusions can be drawn from the above test results and comparative analysis with existing references:

[0121] 1. By comparing reference [7] with reference [5] and reference [6], it can be seen that since the catalysts in reference [5] and reference [6] are both powders, the cycle retention rates are only 80.0% and 86.0% respectively, while the catalyst in reference [7] can significantly increase the cycle retention rate to 92.0% because it is in block form. Therefore, the catalyst with block structure can effectively improve the cycle performance of the composite material;

[0122] However, the technical solution of reference [7] has two technical problems: first, the density of the support material nickel foam is high, resulting in a relatively low mass of the catalytic active substance with catalytic effect; second, due to the extremely low mass loading of the active substance, the HRG is only 4839.8 mL·min -1 g -1 , that is, the catalytic performance is poor.

[0123] 2. Comparing the present invention with reference [7], it can be seen that the present invention uses lightweight MF instead of NF as a carrier, and has a higher HGR of 130% of that in reference [7] while maintaining a cycle retention rate of 90.6%. In addition, since the density of the carrier MF of the present invention is only 0.004-0.012 g / cm 3 , much lower than NF's 0.5-2g / cm3 , thus, significantly reducing the density of the composite material.

[0124] Based on the above analysis, it can be seen that the significant improvement in the cycle performance of the present invention can be attributed to the following reasons:

[0125] 1. Melamine foam MF is used as a carrier to achieve a block structure of the composite material, which greatly reduces the process difficulty, quality loss and damage to the microscopic morphology of the material during the recycling process, and can better maintain the original state of the catalyst; effectively improve the cyclic stability of the catalyst during the reaction process.

[0126] 2. Using melamine foam MF as a carrier not only ensures the lightness of the composite material, thereby increasing the proportion of catalytically active substances with catalytic effects and improving HGR; but also, using PVA to modify its surface makes the nanoparticles have a strong binding force with the carrier and has good stability. The overall microscopic morphology is not easy to collapse during the reaction, and can continuously and effectively carry out catalysis.

[0127] In order to demonstrate the effect of PVA on the surface modification of MF, that is, the role of PVA in the technical solution, comparative example 1 is provided, which is a lightweight block Ru / ZIF-67 / MF composite material using MF as a carrier directly without adding PVA.

[0128] Comparative Example 1

[0129] A method for preparing a lightweight bulk Ru / ZIF-67 / MF composite material using MF as a carrier without adding PVA, wherein the steps not specifically described are the same as those in Example 1, except that: step 1 is not required, and in step 2, MF is added instead of PMF to obtain a bulk Ru / ZIF-67 / MF composite material, referred to as Ru / ZIF-67 / MF for short.

[0130] The test results of Ru / ZIF-67 / MF hydrolysis hydrogen production are as follows Fig.12 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 5074.7 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. Compared with Example 1, by adding PVA, PVA and MF are cross-linked, thereby significantly improving the maximum hydrogen production rate by 24.01%. The reason is that cross-linking of PVA and MF can introduce hydroxyl groups, which can not only increase the number of active sites and the activity of active sites, but also effectively solve the problem of easy accumulation when MF is directly used as a carrier, directly and effectively increase the specific surface area of ​​the catalyst, and improve the catalytic performance.

[0131] In order to demonstrate the influence of ZIF-67 on the composite material, that is, the role of ZIF-67 in the technical solution, Comparative Example 2 is provided, which is a lightweight block composite material in which Ru is directly loaded on PMF without adding ZIF-67.

[0132] Comparative Example 2

[0133] A method for preparing a lightweight bulk composite material in which Ru is directly loaded on PMF without adding ZIF-67. The steps not specifically described are the same as those in Example 1, except that: step 2 is not performed, and in step 3, PMF is added instead of ZIF-67 / PMF to obtain a lightweight bulk Ru / PMF composite material, referred to as Ru / PMF.

[0134] The SEM test results of Ru / PMF are as follows Fig.13 As shown in Figure 2, Ru / PMF is a grain agglomerate. The test results show that the introduction of ZIF-67 can avoid the agglomeration phenomenon, that is, ZIF-67 has the function of regulating the microstructure.

[0135] The test results of Ru / PMF hydrolysis hydrogen production are as follows Fig.12 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 4271.3 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. Compared with Example 1, it can be seen that the maximum hydrogen production rate can be significantly increased by 47.32% by first growing ZIF-67 in situ on the PMF surface and then loading the Ru element. The reason is that by growing ZIF-67 in situ on the PMF surface, the microscopic morphology of the composite material is directly adjusted, which can effectively avoid agglomeration, thereby significantly increasing the specific surface area of ​​the composite material.

[0136] In order to demonstrate the effect of the amount of ruthenium trichloride hydrate added on the catalytic performance, comparative examples 3, 4 and 5 are provided, and lightweight block Ru / ZIF-67 / PMF composite materials are prepared with a mass ratio of ruthenium trichloride hydrate to MF of 6:10, 9:10 and 15:10, respectively.

[0137] Comparative Example 3

[0138] A method for preparing Ru / ZIF-67 / PMF with a ruthenium trichloride hydrate addition ratio of 6:10, wherein the steps not specifically described are the same as those in Example 1, except that: in step 3, the mass ratio of ruthenium trichloride hydrate to MF is 6:10, that is, the addition amount of ruthenium trichloride hydrate is 6 mg, and the obtained composite material is referred to as Ru / ZIF-67 / PMF-6.

[0139] The test results of Ru / ZIF-67 / PMF-6 for hydrogen production by hydrolysis are as follows Fig.12As shown in Figure 2, at 303K, the maximum hydrogen production rate is 4598 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. Compared with Example 1, it can be seen that increasing the amount of ruthenium trichloride hydrate added can increase the maximum hydrogen production rate by 36.85%.

[0140] Comparative Example 4

[0141] A method for preparing Ru / ZIF-67 / PMF with a ruthenium trichloride hydrate addition ratio of 9:10, wherein the steps not specifically described are the same as those in Example 1, except that: in step 3, the mass ratio of ruthenium trichloride hydrate to MF is 9:10, that is, the addition amount of ruthenium trichloride hydrate is 9 mg, and the obtained composite material is referred to as Ru / ZIF-67 / PMF-9.

[0142] The test results of Ru / ZIF-67 / PMF-9 for hydrogen production by hydrolysis are as follows Fig.12 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 5332.9 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. Compared with Example 1, it can be seen that increasing the amount of ruthenium trichloride hydrate added can increase the maximum hydrogen production rate by 17.99%.

[0143] Comparative Example 5

[0144] A method for preparing Ru / ZIF-67 / PMF with a ruthenium trichloride hydrate addition ratio of 15:10, wherein the steps not specifically described are the same as those in Example 1, except that: in step 3, the mass ratio of ruthenium trichloride hydrate to MF is 15:10, that is, the addition amount of ruthenium trichloride hydrate is 15 mg, and the obtained composite material is referred to as Ru / ZIF-67 / PMF-15.

[0145] The test results of Ru / ZIF-67 / PMF-15 for hydrogen production by hydrolysis are as follows Fig.12 As shown in Figure 2, at 303K, the maximum hydrogen production rate is 5985.4 mL min -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value. Compared with Example 1, it can be seen that when the amount of ruthenium trichloride hydrate added is further increased, that is, when the amount of ruthenium trichloride hydrate is excessive, the maximum hydrogen production rate is reduced, and the reduction range reaches 5.13%.

[0146] It can be seen from Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 that the addition amount of ruthenium trichloride hydrate has a significant effect on the catalytic performance, which can be simply summarized as follows:

[0147] When the amount of ruthenium trichloride hydrate added is small, the loading amount of Ru nanoparticles is small, resulting in fewer catalytic active sites;

[0148] When the amount of ruthenium trichloride hydrate added is too much, the Ru nanoparticle loading is too high, resulting in the accumulation and agglomeration of the Ru nanoparticles, thereby reducing the active sites and reducing the atomic utilization.

Claims

1. A lightweight bulk Ru / ZIF-67 / PMF composite material, characterized in that: Using melamine foam PMF treated with polyvinyl alcohol (PVA) as a carrier, ZIF-67 was grown on the surface of PMF to prepare ZIF-67 / PMF, and then Ru nanoparticles were loaded by chemical reduction to obtain Ru / ZIF-67 / PMF lightweight block composite material. The raw materials of the PMF are melamine foam, polyvinyl alcohol, formaldehyde and sulfuric acid; The raw materials of ZIF-67 are cobalt nitrate hexahydrate and 2-methylimidazole; The raw materials of Ru are ruthenium trichloride hydrate and sodium borohydride.

2. The lightweight bulk Ru / ZIF-67 / PMF composite material according to claim 1, characterized in that: The microstructure of the Ru / ZIF-67 / PMF is a 3D porous structure, and a rhombic dodecahedron structure with a size of 500-800 nm is grown and coated on the surface of PMF. The component of the rhombic dodecahedron structure is ZIF-67. Ru nanoparticles are used as active materials and are loaded on the surface of ZIF-67 by in-situ reduction of sodium borohydride.

3. The lightweight bulk Ru / ZIF-67 / PMF composite material according to claim 1, characterized in that: The obtained Ru / ZIF-67 / PMF is a macroscopic block structure, and controllable on-demand hydrogen release can be achieved by controlling the height.

4. A method for preparing a lightweight bulk Ru / ZIF-67 / PMF composite material, characterized in that The following steps are involved: Step 1, preparation of PMF, first, polyvinyl alcohol PVA and deionized water are mixed, and mixed and stirred under certain conditions to obtain solution A; then, formaldehyde, sulfuric acid and solution A are mixed to obtain solution B; thereafter, melamine foam MF is placed in solution B, and allowed to stand under certain conditions so that MF absorbs solution B to obtain polyvinyl alcohol melamine foam PVA-MF; finally, under certain conditions, PVA-MF is subjected to co-acetalization cross-linking reaction, and after the reaction is completed, the reaction product is washed with water and ethanol, and then vacuum dried under certain conditions to obtain PMF; Step 2, preparation of ZIF-67 / PMF, PMF obtained in step 1 and cobalt nitrate hexahydrate are placed in methanol, and an operation of first ultrasonication and then standing is performed under certain conditions to obtain solution C; in addition, 2-methylimidazole is placed in methanol to obtain solution D; then, solution D is quickly added to solution C, and an operation of first stirring and then standing is performed under certain conditions to obtain product E; finally, product E is washed with water and ethanol, and then vacuum dried under certain conditions to obtain ZIF-67 / PMF; Step 3, preparation of Ru / ZIF-67 / PMF, after dispersing the ZIF-67 / PMF obtained in step 2 in deionized water, add ruthenium trichloride hydrate, perform an operation of ultrasonication and then standing under certain conditions to obtain solution F, and then, under certain conditions, add sodium borohydride solution dropwise to solution F, after the addition is completed, stand under certain conditions again, after standing, wash the obtained product thoroughly with ethanol, and vacuum dry under certain conditions to obtain a lightweight block Ru / ZIF-67 / PMF composite material.

5. The preparation method according to claim 4, characterized in that: In the step 1, the mass ratio of PVA, formaldehyde, sulfuric acid and MF is 1:2:1:(5-10); In the step 2, the mass ratio of PMF, cobalt nitrate hexahydrate and 2-methylimidazole is (1-4):60:(20-40); In step 3, the mass ratio of ZIF-67 / PMF, ruthenium trichloride hydrate and sodium borohydride solution is 10:(1-2):(5-10).

6. The preparation method according to claim 4, characterized in that: In step 1, the conditions for preparing solution A are: mixing temperature is 80-100° C., and mixing time is 3-6 h; In the step 1, the strips of solution B are allowed to stand for a period of 0.5-1 h; In step 1, the conditions for the co-acetalization cross-linking reaction are: a heating temperature of 80-100° C. and a heating time of 3-6 h; In step 1, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 6-12 h.

7. The preparation method according to claim 4, characterized in that: In step 2, the conditions for preparing solution C by ultrasonication and then standing are as follows: the ultrasonication time is 30-60 min and the standing time is 12-24 h; In step 2, the conditions for preparing solution C by stirring first and then standing are: the stirring time is 2-3 hours and the standing time is 12-24 hours; In step 2, the vacuum drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 12-24 hours.

8. The preparation method according to claim 4, characterized in that: In step 3, the conditions for preparing solution F by first ultrasonicating and then standing are as follows: the ultrasonication time is 30-60 min and the standing time is 12-24 h; In step 3, the conditions for adding sodium borohydride dropwise are: the ice bath temperature is 2-6° C., the drop rate is 3-5 drops / s, and the concentration of sodium borohydride is 0.5-1 M; In step 3, the standing condition is that the standing time is 12-24 hours; In step 3, the vacuum drying conditions are as follows: the drying temperature is 80-100° C. and the drying time is 12-24 hours.

9. A lightweight bulk Ru / ZIF-67 / PMF composite material, characterized in that: When used as a catalyst for hydrogen production from sodium borohydride hydrolysis, the maximum hydrogen production rate is 6000-7000 mL·min at 303K. -1 ·g -1 , the amount of hydrogen released is 100% of the theoretical value; After 5 cycles, 80.7-91.5% of the initial maximum hydrogen production rate was still retained.

10. A lightweight bulk Ru / ZIF-67 / PMF composite material, characterized in that: When used as a catalyst for hydrogen production by hydrolysis of sodium borohydride, the apparent activation energy E a =20.9-25.3 kJ·mol -1 .

Citation Information

Patent Citations

  • Sponge carrier catalyst for catalytic hydrolysis hydrogen production and preparation method and application thereof

    CN111841634A

  • Composite sponge catalyst as well as preparation method and application thereof

    CN113571718A

  • Composite material based on covalent-metal organic framework double carriers as well as preparation method and application of composite material

    CN116159600A